ORGANIZATION OF TOURIST AREAS AT ARCHAEOLOGICAL SITES (American Journal of Interdisciplinary Research and Development, 2023)
This article discusses the history of preservation and updating of archaeological monuments of Uzbekistan. At the same time, there is an urgent need for restoration work on archaeological monuments, dictated, first of all, by an attentive and careful attitude to the ancient history of Uzbekistan.